Analysis of HPE Hyperconverged Information Technology Marketing Strategy at Proteksindo Data Supplier Company - Sarwo Edi Rizal (Green Publisher Indonesia, 2021)
Hewlett Packard Enterprice (HPE) Hyperconverged is an Information Technology (IT) framework that combines storage, computing and networking into a single system in an effort to reduce data center complexity and increase scalability. HPE Hyperconverged improve business and the productivity of IT staff and increase the speed of services delivered to customer. The marketing strategies that will be researched to see of the marketing mix, consisting of product, price, place, promotion, people and processes, the analysis using the Strengh Weaknesses Opportunities Threat (SWOT) analysis to determine the right strategy. The method study was descriptive qualitative research. The subjects in this study were the manager marketing, 2 marketing staffs and 3 sales . The instrument used a form of interview guidelines and the type of recorder. Data analysis used SWOT analysis. Results in this reasearch that (1) Products: Products used in cooperation with Hewlett Packard Enterprise (HPE) that one of biggest IT company in the world (2) Price; price is still relatively expensive. (3) Place; Data Proteksindo in Central Jakarta strategically located. (4) Promotion: Promotion is not maximized. (5) People; trained IT staff, good, loyal. (6) Process: The process of installation of HPE hyperconverged should be accepted to the criteria that will be used in Data Center. Data Proteksindo is in strategic location, the promotion should be more leverage, based on SWOT analysis the most appropriate strategy is an aggressive strategy in order to growth stage.